Character Building Based on The State Philosophy in The Context of Islamic Education - Giantomi Muhammad; Harkit Rahmawati; R. Rofiani; Aan Hasanah; Bambang Samsul Arifin (STAI Hubbulwathan Duri, 2022)
Character education is an important issue that is of concern to various groups, especially in the field of Islamic education. This is because character education is often understood the same as moral education as a very important material in Islamic education. As for character education in Indonesia, besides making religion a source of values (Core ethical values), it also has a state philosophy (Pancasila) as the basis for character education. Therefore, it is necessary to have a clear concept of character education based on state philosophy in the context of Islamic education so that it can be implemented synergistically. The current trend shows a shift in the philosophical values of the Indonesian State (Pancasila), which can be seen in the decline in the quality of the character of the Indonesian people. On the other hand, Islamic education also has a responsibility to maintain and improve the moral quality of students. Therefore, it is important to strive for an understanding of the philosophical values of the state in the context of Islamic education, especially among the younger generation. On the basis of these objectives, through a study of various relevant literatures with analytical descriptive techniques, this study was conducted to analyze how character education is based on state philosophy in the context of Islamic education. The results of the study prove that there is no Pancasila ideology that is contrary to Islamic values. All Pancasila ideologies form a perfect Islam, especially in socializing.